PENGARUH KEPUASAN KERJA DAN STRESS KERJA TERHADAP TURNOVER INTENTION KARYAWAN KONTRAK DI HOTEL ANUMANA UBUD - Gede Elvina Adi Saputri, Luh; Mulyadi, Made; Mahesa Adi Putra, I Kadek; Rasmen Adi, I Nyoman (CV. Lafadz Jaya, 2024)
The purpose of this study is to determine the effect of stress and job satisfaction on turnover intention among contract employees at Anumana Hotel Ubud. This study involved 65 participants who were taken by total sampling method. A Likert scale questionnaire was used to collect data. Multiple linear regression analysis was used to analyze the data. Hypotheses were tested using t-test and F-test. The results of the study present that job satisfaction negatively affects employee turnover intention. turnover intention positively affects job stress. Jointly, job satisfaction and job stress levels affect employee turnover intention. The impact of job stress and job satisfaction together has an impact of 36.6% on turnover intention.